Plastic crystal - gel polymer electrolytes for magnesium rechargeable batteries / Diyana Hambali - Diyana , Hambali (2020)
Polymer electrolytes are known to be the possible substitution for liquid electrolytes due to their excellent safe performance and good compatibility with electrodes compared to its liquid counterpart. Thus, in the present work, gel polymer electrolytes (GPEs) have been studied comprising plastic crystal succinonitrile (SN) to form plastic crystal - gel polymer electrolytes. The GPEs were prepared by using two types of magnesium salts which are magnesium trifluoromethanesulfonate (MgTf2) and magnesium bis(trifluoromethanesulfonimide) (Mg(TFSI)2) varied from 5 to 30 wt.%. In the preparation of GPEs, four GPE systems were introduced which are single plasticized systems (PVdC-co-AN/SN/MgTf2 and PVdC-co-AN/SN/Mg(TFSI)2) and double plasticized systems, i.e., combination of SN with ethylene carbonate (EC), (PVdC-co-AN/SN/EC/MgTf2 and PVdC-co-AN/SN/EC/Mg(TFSI)2). The GPE samples were analyzed by means of alternating current (AC) impedance spectroscopy to determine the ionic conductivity at room temperature and at a temperature range of 303 K to 353 K. The conductivity temperature dependence studies of the GPEs were found to obey the Vogel-Tamman-Fulcher (VTF) relation. The ionic and cationic transference numbers were evaluated by direct current (DC) polarization method and the combination methods of AC impedance and DC polarization respectively to study the charge carrier species in the GPEs. To reveal the interactions among the constituents in the GPEs as well as to confirm the complexation between them, Fourier Transform Infrared Spectroscopy (FTIR) was carried out. The analysis of FTIR was extended by the deconvolution of the FTIR spectra to prove the dependability of ionic conductivity with the presence of free ions, ion pairs and ion aggregates in the GPEs. The amorphous nature of the GPEs was confirmed by X-ray diffraction (XRD) analysis while the surface morphology of GPEs was analyzed by Field Emission Scanning Electron Microscopy (FESEM). On the other hand, differential scanning calorimetry (DSC) studies disclosed the relationship between the thermal stability of GPEs and ionic conductivity. The electrochemical stability of the GPEs was also determined by linear sweep voltammetry (LSV) and cyclic voltammetry (CV). The Mg/GPE/MgMn2O4 cells were assembled by using the most optimum GPE samples from all systems and their charge-discharge performances were studied. The best specific capacity of 90 mAh g-1 was obtained from the cell that using PVdC-co-AN/SN/EC/15 wt.% Mg(TFSI)2 based GPE as electrolyte.